Preparation method of structure and function integrated energy storage equipment

By using high-performance thermoplastic resins and ionic liquids, combined with activated carbon fiber electrodes and glass fiber membranes, integrated structure and function energy storage equipment is prepared through the hot pressing process, which solves the problem of incompatibility between electrochemical performance and mechanical performance and achieves efficient energy storage effects.

CN119694806APending Publication Date: 2025-03-25DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411880287.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The electrochemical and mechanical properties of the existing integrated structure energy storage devices are incompatible, resulting in low energy storage effects and it is difficult to achieve good compatibility between conductivity and mechanical properties.

Method used

The structural electrolyte prepared from high-performance thermoplastic resin heteronaphthalene polyaryl ethersulfone ketone, ionic liquid and sodium salt, combined with activated carbon coated carbon fiber as electrode material and glass fiber as separator, is used to prepare structural and functional integrated energy storage equipment through a hot pressing process.

Benefits of technology

On the basis of ensuring mechanical properties, the electrochemical performance is significantly improved, good electrochemical performance and mechanical performance compatibility are shown, and the energy storage effect is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694806A_ABST
    Figure CN119694806A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of supercapacitors, and particularly relates to a preparation method of structure and function integrated energy storage equipment. In order to enable energy storage equipment to have electrochemical performance and mechanical performance, structural electrolyte is prepared from high-performance thermoplastic resin phthalazinone polyarylethersulfone ketone, ionic liquid and sodium salt, carbon fiber is used as an electrode material, glass fiber is used as a diaphragm, and a structural energy storage integrated device is prepared. Structural energy storage integrated equipment prepared from the structural electrolyte has high ionic conductivity and good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of supercapacitors, and in particular relates to a method for preparing a structurally and functionally integrated energy storage device. Background Art

[0002] With the rapid development of new energy equipment such as drones and electric vehicles, more comprehensive requirements have been put forward for traditional energy storage devices. Traditional electrochemical energy storage devices can be divided into electric double layer capacitors, pseudocapacitors and batteries according to the energy storage mechanism. Among these devices, capacitors have been developed with emphasis due to their faster charge and discharge rates and long cycle life. However, the commercial development of supercapacitors is restricted by the size and space of the overall equipment, and the energy density is low. Especially in the field of aerospace, the disadvantages of energy storage equipment such as large mass and large volume have seriously hindered its further application. How to improve the energy density of the overall device is a difficult problem that needs to be solved urgently. Structural and functional integrated equipment is a device or system that combines energy storage function with load-bearing function. Thereby, the energy storage capacity of the overall equipment is improved without adding extra weight, and the necessary load-bearing function is provided at the same time.

[0003] At present, the preparation of mainstream structural energy storage integrated devices mainly revolves around the modification of composite materials and electrolytes. Patent application number 202311111598.7 discloses a method for preparing carbon fiber electrodes, in which carbon fibers are carbonized to obtain a porous structural carbon fiber with a high specific surface area. Although the energy storage capacity of the electrode material is improved, the mechanical properties of the structural energy storage integrated device using the structure are slightly insufficient. Patent application number 201310225680.2 discloses a method for preparing a structural energy storage integrated device, using carbon fiber cloth treated with a mixed solution of KClO3 and H2SO4 and then oxidized by air as the electrode material, epoxy resin-based gel polymer as the electrolyte, and glass fiber cloth as the diaphragm. Although the electrochemical performance of the prepared structural energy storage integrated device has been greatly improved, due to the need to use a quasi-solid electrolyte, the reproducibility of its curing process is poor, resulting in large performance differences. Structural electrolytes have become a research hotspot for structural energy storage integrated devices because they have both ionic conductivity and mechanical properties. However, it is difficult for current structural electrolytes to achieve good compatibility between conductivity and mechanical properties. Improving the specific surface area and structural stability of electrode materials cannot fundamentally solve the interface incompatibility problem of electrodes and electrolytes, resulting in low energy storage effect of structural energy storage integrated devices, which is still far from practical application. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem of incompatibility between the electrochemical properties and mechanical properties of structural electrolytes, and proposes a method for preparing a structural energy storage integrated energy storage device. The structural electrolyte used is prepared from high-performance thermoplastic resin poly(naphthalene biphenyl) poly(arylether sulfone ketone), ionic liquid and sodium salt, and activated carbon-coated carbon fiber is used as the electrode material and glass fiber is used as the diaphragm to prepare a structural energy storage integrated device. The structural energy storage integrated device prepared from the structural electrolyte exhibits good electrochemical properties while ensuring mechanical properties.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a structural and functional integrated energy storage device, wherein the structural and functional integrated energy storage device comprises a structural electrolyte, an electrode and a diaphragm; specifically comprises the following steps:

[0007] Step 1: mixing an electrolyte salt and an ionic liquid in a mass ratio of 1:(1-3), stirring at 20°C-50°C for 3-6 hours, to obtain a solution A;

[0008] Step 2: mixing poly(phenylene ether sulfone ketone) and N-methyl pyrrolidone in a mass ratio of 1:(3-6), stirring at 20° C. to 50° C. for 3-6 hours, to obtain a solution B;

[0009] Step 3: Mix solution A and solution B in a mass ratio of 1:(2-4), and stir in a forced air drying oven at 20°C-50°C for 6-12 hours to obtain solution C;

[0010] Step 4: Use solution C as a structural electrolyte and evenly apply it on the surface of the activated carbon electrode contacting the diaphragm; add a diaphragm between the two activated carbon electrodes, hot press and form, and obtain a structural and functional integrated energy storage device.

[0011] The diaphragm is a glass fiber diaphragm.

[0012] The activated carbon electrode uses carbon fiber as the electrode material, and the activated carbon slurry is coated on the carbon fiber.

[0013] The electrolyte salt is one of sodium hexafluorophosphate, sodium perchlorate and sodium bis(trifluoromethylsulfonyl)imide or a mixture of two or more thereof.

[0014] The ionic liquid is one of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium tetrafluoroborate and 1-ethyl-2-methylimidazolium bis(trifluoromethanesulfonyl)imide salt or a mixture of two or more thereof.

[0015] The step 4 specifically comprises the following steps:

[0016] (1) Preparation of electrodes and diaphragms: Activated carbon (AC), conductive carbon black (SP) and polyvinylidene fluoride (PVDF) were mixed and dissolved in N-methyl-2-pyrrolidone (NMP) solution in a mass ratio of 8:1:1, ground evenly and coated on carbon cloth, and dried in a vacuum drying oven at 60°C to 80°C for 6 to 12 hours to obtain an activated carbon electrode. The diaphragm was dried at 60°C to 80°C for 6 to 12 hours.

[0017] (2) Capacitor assembly and molding: The structural electrolyte is evenly coated on the side of the activated carbon electrode that contacts the diaphragm, and the electrode, diaphragm, and electrode are stacked together in sequence. A hot pressing molding process is used at a temperature of 50 to 100°C, a pressure of 2 to 4 MPa, and a time of 2 to 6 hours to obtain a structural and functional integrated energy storage device.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention adopts a hot pressing process to prepare an integrated structure. The preparation method is simple to operate, all experimental steps are completed in the air, and the required experimental conditions are simple.

[0020] (2) The structural electrolyte developed by the present invention has high ionic conductivity and good mechanical properties. The use of glass fiber as a separator can also play a synergistic reinforcement role and further improve its mechanical properties.

[0021] (3) The structural energy storage integrated device prepared by the present invention has a basically linear charge and discharge curve, has obvious double-layer capacitance characteristics, has good electrochemical performance, and can be designed in series and parallel to increase the voltage window.

[0022] (4) The structural and functional integrated device prepared by the present invention does not require additional packaging, and has both mechanical properties and reduces the overall weight and volume of the energy storage device. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the cyclic voltammetry curve of the structural energy storage integrated device prepared in Example 1;

[0024] Figure 2 is the charge and discharge curve of the structural energy storage integrated device prepared in Example 1;

[0025] Figure 3 is the cyclic voltammetry curve of the structural energy storage integrated device prepared in Example 2;

[0026] Figure 4 is the cyclic voltammetry curve of the structural energy storage integrated device prepared in Example 3;

[0027] Figure 5 This is the charge and discharge curve of the structural energy storage integrated device prepared in Example 3. DETAILED DESCRIPTION

[0028] The following further describes the implementation of the present invention in conjunction with specific examples and drawings.

[0029] Example 1

[0030] Step 1: Preparation of structured electrolyte

[0031] Dissolve 2 g of poly(phenylene ether sulfone ketone) in 6 g of N-methylpyrrolidone and stir at 20°C for 3 h. Mix 2 g of 1-ethyl-2-methylimidazole bis(trifluoromethylsulfonyl)imide ionic liquid and 2 g of sodium bis(trifluoromethylsulfonyl)imide and stir at 20°C for 3 h. Mix the two solutions and stir at 20°C for 6 h for later use.

[0032] Step 2: Preparation of electrode sheets and diaphragms

[0033] Activated carbon (AC), conductive carbon black and polyvinylidene fluoride (PVDF) were mixed and dissolved in N-methyl-2-pyrrolidone (NMP) solution in a mass ratio of 8:1:1, and ground evenly to obtain 1 g of active material powder.

[0034] Step 3: Processing of carbon fiber cloth and glass fiber diaphragm

[0035] The carbon fiber cloth was cut into 2×2 cm squares, and the glass fiber cloth was cut into 2.2×2.2 cm square separators. The carbon fiber and separators were dried at 60° C. for 6 hours and set aside.

[0036] Step 4: Electrode slurry coating

[0037] The carbon fiber was evenly spread on a glass plate, the slurry was continuously and evenly coated on the surface of the carbon fiber, and the electrode sheet was obtained after being placed in a 60° C. oven and baked for 6 hours.

[0038] Step 5: Preparation of structural and functional integrated devices

[0039] The structural electrolyte of step 1 is evenly soaked on the electrode sheets at both ends, and the cut glass fiber cloth is laid in the middle. The hot pressing process is adopted at a temperature of 50°C, a pressure of 2MPa, and a time of 2h to obtain a structural and functional integrated energy storage device, and the electrochemical performance test is carried out.

[0040] Depend on Figure 1 It can be seen from the cyclic voltammetry curve that as the scan rate increases from 1mV / s to 2mV / s and then to 5mV / s, the shape of the electrochemical curve of the integrated structure changes little and basically remains stable. Figure 2The charge and discharge curve of the integrated structure is shown, and the capacity retention rate is 80% after 100 cycles. The results verify the stable electrochemical behavior of the structural and functional integrated device prepared by this method and show good electrochemical performance.

[0041] Example 2

[0042] Step 1: Preparation of structured electrolyte

[0043] Dissolve 1 g of poly(phenylene ether sulfone ketone) in 6 g of N-methylpyrrolidone and stir at 50°C for 6 h. Mix 0.4375 g of 1-butyl-3-methylimidazole tetrafluoroborate and 1.3125 g of sodium hexafluorophosphate and stir at 50°C for 6 h. Mix the two solutions and stir at 50°C for 12 h for later use.

[0044] Step 2: Preparation of electrode sheets and diaphragms

[0045] Activated carbon (AC), conductive carbon black and polyvinylidene fluoride (PVDF) were mixed and dissolved in N-methyl-2-pyrrolidone (NMP) solution in a mass ratio of 8:1:1, and ground evenly to obtain 1 g of active material powder.

[0046] Step 3: Processing of carbon fiber cloth and glass fiber diaphragm

[0047] The carbon fiber cloth was cut into 2×2 cm squares, and the glass fiber cloth was cut into 2.2×2.2 cm square separators. The carbon fiber and separators were dried at 80° C. for 12 hours and set aside.

[0048] Step 4: Electrode slurry coating

[0049] The carbon fiber was evenly laid on a glass plate, the slurry was continuously and evenly coated on the surface of the carbon fiber, and the electrode sheet was obtained after being placed in an oven at 80° C. and baked for 12 hours.

[0050] Step 5: Preparation of structural and functional integrated devices

[0051] The structural electrolyte of step 1 is evenly soaked on the electrode sheets at both ends, and the cut glass fiber cloth is laid in the middle. The hot pressing process is adopted at a temperature of 100°C, a pressure of 4MPa, and a time of 6 hours to obtain a structural and functional integrated energy storage device.

[0052] Depend on Figure 3 It can be seen from the cyclic voltammetry curve that even if the scan rate increases to 10mV / s, the electrochemical curve of the integrated structure still maintains a stable change, indicating that its electrochemical reversibility is good.

[0053] Example 3

[0054] Step 1: Preparation of structured electrolyte

[0055] Dissolve 1.5 g of poly(phenylene ether sulfone ketone) in 6 g of N-methylpyrrolidone and stir at 30° C. for 4 h. Mix 0.8 g of 1-ethyl-3-methylimidazolium tetrafluoroborate ionic liquid and 1.6 g of sodium perchlorate and stir at 30° C. for 4 h. Mix the two solutions and stir at 30° C. for 8 h for later use.

[0056] Step 2: Preparation of electrode sheets and diaphragms

[0057] Activated carbon (AC), conductive carbon black and polyvinylidene fluoride (PVDF) were mixed and dissolved in N-methyl-2-pyrrolidone (NMP) solution in a mass ratio of 8:1:1, and ground evenly to obtain 1 g of active material powder.

[0058] Step 3: Processing of carbon fiber cloth and glass fiber diaphragm

[0059] The carbon fiber cloth was cut into 2×2 cm squares, and the glass fiber cloth was cut into 2.2×2.2 cm square separators. The carbon fiber and separators were dried at 70° C. for 8 hours and set aside.

[0060] Step 4: Electrode slurry coating

[0061] The carbon fiber was evenly laid on a glass plate, the slurry was continuously and evenly coated on the surface of the carbon fiber, and the electrode sheet was obtained after being placed in a 70° C. oven and baked for 8 hours.

[0062] Step 5: Preparation of structural and functional integrated devices

[0063] The structural electrolyte of step 1 is evenly soaked on the electrode sheets at both ends, and the cut glass fiber cloth is laid in the middle. The hot pressing process is adopted with a temperature of 60°C, a pressure of 3MPa, and a time of 4h to obtain a structural and functional integrated energy storage device.

[0064] Depend on Figure 4 It can be seen from the cyclic voltammetry curve that even if the scan rate increases to 10mV / s, the cyclic voltammetry curve remains stable and its electrochemical reversibility is good. Figure 5 This is the charge and discharge curve of the integrated structure. The capacity decay in the first four cycles is 0. The result once again verifies the stable electrochemical performance of the structural and functional integrated device prepared by this method.

Claims

1. A method for preparing a structural and functional integrated energy storage device, wherein the structural and functional integrated energy storage device comprises a structural electrolyte, an electrode and a diaphragm; characterized in that: The specific steps include: Step 1: mixing an electrolyte salt and an ionic liquid in a mass ratio of 1:(1-3), stirring at 20°C-50°C for 3-6 hours, to obtain a solution A; Step 2: mixing poly(phenylene ether sulfone ketone) and N-methyl pyrrolidone in a mass ratio of 1:(3-6), stirring at 20° C. to 50° C. for 3-6 hours, to obtain a solution B; Step 3: Mix solution A and solution B in a mass ratio of 1:(2-4), and stir in a forced air drying oven at 20°C-50°C for 6-12 hours to obtain solution C; Step 4: Use solution C as a structural electrolyte and evenly apply it on the surface of the activated carbon electrode contacting the diaphragm; add a diaphragm between the two activated carbon electrodes, hot press and form, and obtain a structural and functional integrated energy storage device.

2. A method for preparing a structural and functional integrated energy storage device according to claim 1, characterized in that: The diaphragm is a glass fiber diaphragm.

3. A method for preparing a structural and functional integrated energy storage device according to claim 1, characterized in that: The activated carbon electrode uses carbon fiber as the electrode material, and the activated carbon slurry is coated on the carbon fiber.

4. A method for preparing a structural and functional integrated energy storage device according to claim 1, characterized in that: The electrolyte salt is one of sodium hexafluorophosphate, sodium perchlorate and sodium bis(trifluoromethylsulfonyl)imide or a mixture of two or more thereof.

5. A method for preparing a structural and functional integrated energy storage device according to claim 1, characterized in that: The ionic liquid is one of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium tetrafluoroborate and 1-ethyl-2-methylimidazolium bis(trifluoromethanesulfonyl)imide salt or a mixture of two or more thereof.

6. A method for preparing a structural and functional integrated energy storage device according to claim 1, characterized in that: The step 4 specifically comprises the following steps: (1) Preparation of electrodes and diaphragms: Activated carbon, conductive carbon black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1 and dissolved in an N-methyl-2-pyrrolidone solution, ground evenly and coated on a carbon cloth, and dried in a vacuum drying oven at 60°C to 80°C for 6 to 12 hours to obtain an activated carbon electrode; the diaphragm was dried at 60°C to 80°C for 6 to 12 hours; (2) Capacitor assembly and molding: The structural electrolyte is evenly coated on the side of the activated carbon electrode that contacts the diaphragm, and the electrode, diaphragm, and electrode are stacked together in sequence. A hot pressing molding process is used at a temperature of 50 to 100°C, a pressure of 2 to 4 MPa, and a time of 2 to 6 hours to obtain a structural and functional integrated energy storage device.

Citation Information

Patent Citations

  • Energy storage / structure integration-combined multifunctional energy storage device and preparation method thereof

    CN103337379A

  • Carbon fiber electrode for structural energy storage integrated composite material as well as preparation and application of carbon fiber electrode

    CN116994885A